Bearing capacity of Skirt circular footing on sand - Amr Z. EL Wakil (Alexandria Engineering Journal, 2013)
Skirts are used to improve the bearing capacity of shallow footings on sandy soil by constraining the soil beneath and containing the plastic flow of soil. They are used as an alternative to deep foundations in soils with low strength at the surface. As there has been available little work studying the performance of skirted foundation, we are performing eighteen laboratory experiments on circular steel footings of different diameters and different skirt lengths. The aim of these experiments is to shed some lights on the effects of skirts on the bearing capacity of shallow footings. The effects of skirt length and the relative density of sand on the ultimate load attained were investigated. From the accomplished laboratory tests, it was found that skirts improve appreciably the sustainability of shallow footings to applied load as they increase the ultimate load of shallow footings by some up to 6.25 times for the current study conditions and variables. The performance of skirted footing depends upon the relative density of sand and on the skirt length to footing diameter ratio. Skirts are more beneficial in case of footings on loose sand than in case of medium and dense sand.